The 20 February 2010 Madeira Island flash-floods: VHR satellite imagery processing in support of landslide inventory and sediment budget assessment - C. Lira; M. Lousada; A. P. Falcão; A. B. Gonçalves; S. Heleno; M. Matias; M. J. Pereira; P. Pina; A. J. Sousa; R. Oliveira; A. B. Almeida (Natural Hazards and Earth System Sciences, 2013)
On 20 February 2010, an extreme rainfall episode occurred on Madeira Island, which caused an exceptionally strong flash flood and several soil slip-debris flows, producing 45 confirmed deaths and 6 persons declared missing, as well as extensive material damages. In order to understand and quantify the importance of landsliding in routing sediment through mountainous drainage, such as Madeira Island's landscape, it was essential to perform extensive landslide analysis. This study describes the methodology used to semi-automatically detect the landslides, produce the landslide inventory maps and estimate the sediment volume produced during this particular event which ranged from 217 000 m3 to 344 000 m3 and 605 000 m3 to 984 000 m3 for the Funchal and Ribeira Brava basins, respectively. These results contributed to the design and implementation of measures to prevent damages caused by landslides in Madeira Island.